Cross-cultural Training and Second Language Learning (Asian Education Studies, 2017)
Culture and language are inseparable, and cultures as groups adopt particular practices and norms of behavior. Culture teaching is a long and complex process concerning something more than language use itself. The two popular theories influencing practice today are the Constructivist and the Creative Constructionist approaches, and the technique for conveying cultural awareness is cultural assimilator, which has been designed for specific cultures around the world. Cross-cultural training can be used to promote cultural awareness, that is, sensitize people to the influence of culture on people’s values and behaviors and help them recognize and accept the existence of cultural differences.